From social safety net to social policy? The role of conditional cash transfers in welfare state development in Latin America - Francesca Bastagli (International Policy Centre for Inclusive Growth (IPC-IG), 2009)
During the 1990s, conditional cash transfers (CCTs) were adopted by countries across Latin America as central elements of their poverty reduction strategies. Alongside other developments in the area of social assistance, CCTs represent an opportunity for countries to develop an integrated and inclusive set of social policies. At the same time, particular CCT features risk promoting the further residualisation and fragmentation of safety nets. Drawing on the experience of six countries in Latin America, this paper identifies the variations and recent trends in CCT design and implementation. Based on this review, it considers the contribution of CCTs to the potential transition from a largely absent or minimal safety net to a coordinated system of social policies.
Keywords: 330; cash transfers; targeting; conditionality; social protection; Latin America; Sozialpolitik; Sozialtransfer; Lateinamerika